Tingkat Refleksi Pembelajaran Mahasiswa Angkatan 2018 Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi Menggunakan Skala Reflection-In-Learning - Polii, Vanessa G.; Mariki, Windy M. V.; Wagiu, Christilia G. (Universitas Sam Ratulangi, 2020)
Abstract: Medical students need to know and apply reflection in preparing to become a professional in the health field, especially becoming a doctor. A doctor must be prepared to a long life study, therefore, reflection in learning can be a useful parameter in the professionalism of doctors. This study was aimed to test the reflection in learning of medical students at Sam Ratulangi University batch of 2018. This was a quantitative descriptive study. Respondents were 150 medical students batch of 2018. The Indonesian adaptation reflection-in-learning scale questionnaire was used to test the level of learning reflection of respondents. The results showed that of the reflection in learning,